11 - Appendix II: Economic Community of West African States: Sixth Meeting of Foreign Affairs Ministers of the Committee of Five on Sierra Leone Conakry - Journal System, (Africa Development, 1997)
Appendix II: Economic Community of West African States: Sixth Meeting of Foreign Affairs Ministers of the Committee of Five on Sierra Leone, Conakry 22-23 October 1997